Morphology and topology of dolostone lithons in the regional Carboneras Fault Zone, Southern Spain. (August 2020) - Igbokwe, Onyedika Anthony; Mueller, Mathias; Bertotti, Giovanni; Timothy, Jithender J.; Abah, Obinna; Immenhauser, Adrian
Abstract: Dolostones in a Neogene strike-slip fault zone are described. Two main types of structural features are recognised: (i) Background deformation in the form of a network of bedding-perpendicular and hybrid conjugate fractures, barren fractures and bedding-parallel stylolites. (ii) Fault-related features include breccias and cataclasites. Orthorhombic rock lithons are generated from the intersection of fracture sets with bedding and/or joints. Lithon size and morphology change across the dolostone fault block gradually producing a tetragonal or isometric shape. The lithons are 1–2 cm in dimension (only 20% outside this range) and have an average cross-sectional aspect ratio of 1.6, irrespective of size or structural position. Topology is analysed using nodes and branches, ranging from isolated (I- node and I-I branch) to connected (Y- and X-nodes, and I-C to C-C branches) respectively. The quantitative description of the geometrical and topological analysis of the dolostone lithons suggest that they become more connected and interact within the dolostone fault blocks. Assessing the change in topology and lithons connectivity have important implications for subsurface reservoirs and aquifers hosted in dolostone-fault zones. Highlights: Dolostones are deformed by the Neogene regional strike-slip fault. The deformation caused the development of different sets of background structures. Lithons are generated from the intersection of fracture sets with bedding or joints. Lithons morphology change in shape across fault zone with identical aspect ratio. Topology reveals lithons spatial interaction and well-connectedness among themselves.